A systematic search for galaxy proto-cluster cores at z ∼ 2. Issue Volume 15:Issue S359(2020) (March 2019) - Ando, Makoto; Shimasaku, Kazuhiro; Momose, Rieko
Abstract: A proto-cluster core is the most massive dark matter halo (DMH) in a given proto-cluster. To reveal the galaxy formation in core regions, we search for proto-cluster cores at z ˜ 2 in ˜1.5deg 2 of the COSMOS field. Using pairs of massive galaxies (log ( M */ Mʘ ) ≥ 11) as tracers of cores, we find 75 candidate cores. A clustering analysis and the extended Press-Schechter model show that their descendant mass at z = 0 is consistent with Fornax-like or Virgo-like clusters. Moreover, using the IllustrisTNG simulation, we confirm that pairs of massive galaxies are good tracers of DMHs massive enough to be regarded as proto-cluster cores. We then derive the stellar mass function and the quiescent fraction for member galaxies of the 75 candidate cores. We find that stellar mass assembly and quenching are accelerated as early as z ˜ 2 in proto-cluster cores.